Hepatocellular carcinoma in variegate porphyria: a case report and literature review. (May 2015) - Luvai, Ahai; Mbagaya, Wycliffe; Narayanan, Deepa; Degg, Tim; Toogood, Giles; Wyatt, Judith I; Swinson, Daniel; Hall, Claire J; Barth, Julian H
Variegate porphyria is an autosomal dominant acute hepatic porphyria characterized by photosensitivity and acute neurovisceral attacks. Hepatocellular carcinoma has been described as a potential complication of variegate porphyria in case reports. We report a case of a 48-year-old woman who was diagnosed with hepatocellular carcinoma following a brief history of right upper quadrant pain which was preceded by a few months of blistering lesions in sun-exposed areas. She was biochemically diagnosed with variegate porphyria, and mutational analysis confirmed the presence of a heterozygous mutation in the protoporphyrinogen oxidase gene. Despite two hepatic resections, she developed pulmonary metastases. She responded remarkably well to Sorafenib and remains in remission 16 months after treatment. A review of the literature revealed that hepatocellular carcinoma in variegate porphyria has been described in at least eight cases. Retrospective and prospective cohort studies have suggested a plausible association between hepatocellular carcinoma and acute hepatic porphyrias. Hepatic porphyrias should be considered in the differential diagnoses of hepatocellular carcinoma of uncertain aetiology. Patients with known hepatic porphyrias may benefit from periodic monitoring for this complication.